Konsep Healing Environmet: Aplikasi Pencahayaan, Warna, Dan View Pada Pusat Rehabilitasi Narkoba Di Kabupaten Mamuju Tengah - Maqfirah Putri, Dian; Marwati, Marwati; Herniwati, Andi (TIMPALAJA : Architecture Student Journals, 2022)
Abstract_ The dynamics of Central Mamuju Regency as a place for drug trafficking by sea, so that it is used by drug dealers for drug buying and selling transactions. The number of drug cases in Central Mamuju Regency has increased every year. The need for rehabilitation facilities for drug abusers in Central Mamuju Regency as one of the post-medical healing solutions. The design exploration method with qualitative descriptive analysis is used in applying the elements of the healing environment concept (lighting, color and view) to the object of study in the design of the Mamuju rehabilitation center. The results of the study are the aspects of the porous openings, the colors with a warm impression and the wide openings which are applied to the design of drug rehabilitation centers. It is hoped that it can build a physical atmosphere to help patients overcome stress from the drug rehabilitation process and can immediately return to normal life and socialize again with the community.